Validity and reliability of the Malay Iowa Infant Feeding Attitude Scale among mothers with infants in Malaysia: a validation study - Jamani, Nurjasmine Aida; Hashim, Hazwani Hanum; Abd. Aziz, Karimah Hanim; Kamaruzaman, Nor Azam (ACADEMY OF FAMILY PHYSICIANS OF MALAYSIA, 2025)
Introduction: The Iowa Infant Feeding Attitude Scale (IIFAS) has been developed to assess maternal attitudes towards infant feeding choices to predict breastfeeding intention. Validity and reliability need to be established considering cultural, language and environmental differences, especially in the Malay context due to currently unavailable Malay version. This study aimed to translate the IIFAS into Malay (IIFAS-M) and determine its validity and reliability. Methods: A validation study using a digital survey was conducted. The final translated version was distributed to mothers with infants using the digital form. Principal component analysis was performed using SPSS version 27. Results: A total of 272 mothers with a mean age of 30.1 (SD±4.2) years participated in the study. A new scoring was given to the IIFAS-M, representing positive attitudes towards breastfeeding and neutral and positive attitudes towards formula feeding. The principal component analysis showed that all items had a factor loading of more than 0.4. The Cronbach’s alpha value was 0.657, and the P-value for the test–retest Pearson correlation was <0.001. Conclusion: The IIFAS-M is a validated and reliable tool for assessing maternal attitudes towards infant feeding among Malay speakers.